Gig economy and freelancing work in Algeria: A descriptive survey study - Yahiaoui, Nour El Houda (Journal of Management, Economics, and Industrial Organization, 2025)
In Algeria, gig economy emergence was fueled by local telecommunications infrastructure’ and internet connectivity improvement, and labor market deteriorating conditions. This study aims to describe Algerian freelancers' experience in the gig economy, the precarities, and inequalities freelancers experience with platforms.This research is an exploratory descriptive study. It uses an online questionnaire to conduct a descriptive survey on 60 Algerian freelancer active on freelancing platforms. Respondents were reached via LinkedIn. The collected data were analyzed using Excel. The study finds that freelancing in Algeria is driven by the growing availability of digital platforms like Upwork and Fiverr. Local demand for freelancers remains limited. The gig economy in Algeria is youth-driven; gig workers are young people aged between 20-29 years old (65%), majoring in IT and Communication, active in the field of creative design, and mainly male (80%), indicating a gender gap similar to the existing one in the traditional labor market. Most freelancers are part-time workers, and in general, freelancing is a second choice in most cases.Algerian freelancers are highly educated, they use their professional network, work experience and client ratings and feedback to get new projects without needing for university degrees as signals in the online gig labor. They usually rely on ongoing self-study to develop and preserve pertinent skills.We contribute to the discourse into the gig economy by concentrating on the Algerian context as a growing labor market contrasting with countries in the global north. We provide insights into the relationships’ dynamics and the asymmetries the gig economy market reproduces.
Keywords: online labour markets; gig work; gig economy; freelancers; platform economy